Visualization of the holodomor 1932–1933 (on the materials of film documentalism and journalism) - Kosiuk, Oksana (Baltija Publishing, 2024)
The article is the first to examine and compare ways of presenting reality in the fields of journalism and documentary film. The historical dilemma of «author-developed vs fact-based» in documentaries of each director is solved in its own way. However, unfortunately, most often the solution is not in favour of journalism. The purpose. However, we will try to determine what parameters it is appropriate to identify and distinguish between documentary filmmaking and journalism. The material of our research will be the most rated documentaries and, in part, feature films and good-sized modern video projects of the amorphous genre, which captures the issue of the Holodomor in Ukraine in 1932-1933. The research methodology will be based on the theoretical foundations of the simultaneous relationship and self-sufficiency of the phenomena of reality and their media presentations and logical interpretations. Carrying out the research, we plan to use a number of methods and approaches, among which there are some determinative ones such as contrast, analogy and comparison of both specific modern and ancient media products, and journalism and documentary filmmaking in general. Analysis and synthesis, modelling for the interpretation and evaluation of phenomena and other methods will also be important. Results. It was found that, despite the apparent similarity and current modifications in the information space of the era of new technologies, these are functionally different areas. Documentary filmmaking actively uses all the latest journalistic methods of gathering information and uses certain aspects of its implementation. However, by its nature, documentary remains the equivalent of journalism, so it uses a set of resources that balance between journalism and art: on one hand – relevance, efficiency, factualism, balance of ideas, etc., on the other – imagery, individualism, fiction and others. If we compare the first (non-fiction) films and modern documentaries and journalistic videos (for example, on the topic of the Holodomor in Ukraine), we see that the strength of the audience is dominated by traditional documentaries (obviously due to emotionality, subjectivity, imagery, powerful manipulative effects). Filmmakers who have a degree in journalism, successfully adapt their product to journalism, unfortunately, there are not so many of them. So in addition to positive factors (encouraging objectivity and factuality), convergence of documentary to journalism creates problems in the dimension of perception, evaluation and interpretation. Practical implications. The audience should be carefully prepared for such a statement, which should regulate the strategies of their own perception of information, depending on what is being viewed: a documentary or one of the genres of journalism. Our findings and conclusions can also be considered a field for future research and one of the priority areas for improving documentary and journalistic products.
Keywords: journalism; famine; documentary film; fact; invention; the history of cinema; 001(08)